Cost Effectiveness in River Management: Evaluation of Integrated River Policy System in Tidal Ouse - Tao Wang (Fondazione Eni Enrico Mattei (FEEM), 2006)
The River Ouse forms a significant part of Humber river system, which drains about one fifth the land area of England and provides the largest fresh water source to the North Sea from UK. The river quality in the tidal river suffered from sag of dissolved oxygen (DO) during last few decades, deteriorated by the effluent discharges. The Environment Agency (EA) proposed to increase the water quality of Ouse by implementing more potent environmental policies. This paper explores the cost effectiveness of water management in the Tidal Ouse through various options by taking into account the variation of assimilative capacity of river water, both in static and dynamic scope of time. Reduction in both effluent discharges and water abstraction were considered along side with choice of effluent discharge location. Different instruments of environmental policy, the emission tax-subsidy (ETS) scheme and tradable pollution permits (TPP) systems were compared with the direct quantitative control approach. This paper at the last illustrated an empirical example to reach a particular water quality target in the tidal Ouse at the least cost, through a solution of constrained optimisation problem. The results suggested significant improvement in the water quality with less cost than current that will fail the target in low flow year.
Keywords: C31; C61; L51; R19; 330; Water Quality Management; Tradable Pollution Permits; Tax and Subsidy; Effluent Discharge; Water Abstraction; Dynamic Equilibrium; Integrated River Policy; Cost Effectiveness